Hydrodynamic Aspects of Particle Clogging in Porous Media - MAYS, DAVID C. (2005)
Data from 6 filtration studies, representing 43 experiments, are analyzed with a simplified version of the single-parameter O’Melia and Ali clogging model. The model parameter displays a systematic dependence on fluid velocity, which was an independent variable in each study. A cake filtration model also explains the data from one filtration study by varying a single, velocity-dependent parameter, highlighting that clogging models, because they are empirical, are not unique. Limited experimental data indicate exponential depth dependence of particle accumulation, whose impact on clogging is quantified with an extended O’Melia and Ali model. The resulting two-parameter model successfully describes the increased clogging that is always observed in the top segment of a filter. However, even after accounting for particle penetration, the two-parameter model suggests that a velocity-dependent parameter representing deposit morphology must also be included to explain the data. Most of the experimental data are described by the single-parameter O’Melia and Ali model, and the model parameter is correlated to the collector Peclet number.